LASER IN PHYSIOTHERAPY: EXPERIENCE IN THE TREATMENT OF FIBRILLAR RUPTURE - Fernandez Rabadan, M.; . Pena Algaba, C; Sibajas Chicon, I. (Cuestiones de Fisioterapia, 2000)
In this article we have valued at tissue regeneration afterwards of breaking muscular fibers, the influence of laser in this process.This work is purely descriptive It has its foundation in the follow up from thirty-one patients. These cases were treated in our center during 1999. We used a specific protocol which was worked for this study, in this protocol, laser is the central element to treatment. Too, we'll compare the results with application of the same treatment protocol without to use laser.The three stage that shape the ultrasound scan of these injuries and laser description besides we describe treatment protocol and results obtained after their application.